2020
DOI: 10.1111/jvim.15918
|View full text |Cite
|
Sign up to set email alerts
|

The association of bacteriuria with survival and disease progression in cats with azotemic chronic kidney disease

Abstract: Background: Cats with chronic kidney disease (CKD) have an increased prevalence of positive urine cultures (PUC). Limited information is available regarding the prognosis of cats with CKD and concurrent PUC. Objective: To determine the association of PUC with survival time and disease progression in cats with CKD. Animals: Medical records of 509 cats diagnosed with azotemic CKD between 1997 and 2018. Methods: Cats were classified as having "no-PUC" or "PUC." The PUC cats were further classified as having 1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…These observations then raise the question of what conditions could have triggered the overgrowth, not just the predominance, of E. coli sufficient to cause PUCs in some CKD cases. Older female cats are at a higher risk of developing UTIs among cats with CKD ( 17 ). Also, Price et al ( 7 ) showed that the urinary microbiome was more likely to be predominated by Escherichia in older women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations then raise the question of what conditions could have triggered the overgrowth, not just the predominance, of E. coli sufficient to cause PUCs in some CKD cases. Older female cats are at a higher risk of developing UTIs among cats with CKD ( 17 ). Also, Price et al ( 7 ) showed that the urinary microbiome was more likely to be predominated by Escherichia in older women.…”
Section: Discussionmentioning
confidence: 99%
“…Given the proven existence of the urinary microbiome in humans and dogs ( 15 , 16 ), it seems reasonable to hypothesize that a feline urinary microbiome also exists and may interact differently with the host depending on the health of the urinary system. Certainly, subclinical bacteriuria is not uncommon in cats ( 17 ), and urinary tract diseases, notably CKD and feline idiopathic cystitis (FIC), are common causes of morbidity and mortality in cats. However, previous investigations have failed to characterize a urinary microbiome in cats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobials are frequently prescribed in CKD patients due to the high prevalence of urinary tract infection (UTI), which is reported to be approximately 15-30% in cats [115,116] and 8% in dogs with CKD [117].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…9 The overall prevalence of positive cultures in CKD patients has been shown to be lower than in cats in an acute-on-chronic setting, supporting differences in pathogenesis, which could be reflected on urinalysis. 5,[15][16][17] Given that urinalysis findings can be predictive of positive culture, higher value could potentially be placed on the negative predictive power of the urinalysis in acute settings where a veterinarian must prioritize diagnostics due to the financial constraints of the owner. Therefore, the objective of this study was to determine the association between bacterial growth in urine, urinalysis findings and the presence of LUTS in cats with AKI.…”
Section: Introductionmentioning
confidence: 99%